Determination of Atenolol, Rosuvastatin, Spironolactone, Glibenclamide and Naproxen in Blood by Rapid Analysis Liquid Chromatography - Ma, Yin-Hai; Peng, Yong-Fang; Xu, Yi-Ran; Yang, Guang-Yu; Hu, Qiu-Fen (Asian Journal of Chemistry, 2010)
A rapid liquid chromatographic (HPLC) method for the determination of atenolol, rosuvastatin, spirnolactone, glibenclamide and naproxen was developed. The atenolol, rosuvastatin, spirnolactone, glibenclamide and naproxen were extracted from the sample with acetonitrile and they were separated on a ZORBAX Stable Bound (4.6 mm × 50 mm, 1.8 μm) C18 rapid analysis column with methanol and 0.01 mol L-1 of acetic acid (78:22) as the mobile phase. This method provides good reproducibility and sensitivity. The relative standard derivation of overall intra-day variations were less than 2.5 % and the relative standard derivation of inter-day variations were less than 3.0 %. The standard recoveries were ranged from 94-103 %.